Infiltration galleries: a viable alternative to "push-up" diversion dams - Peterson, F. Jeffrey, author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2000)
This paper deals with Infiltration Galleries as alternatives to gravel "push-up" diversion dams. The Bureau of Reclamation (Reclamation) has recently completed projects in conjunction with conservation entities and water users to demonstrate the application of infiltration galleries in rivers and streams that contain anadromous fish. The projects demonstrate that infiltration galleries buried in the stream bed can provide irrigation flows and reduce impacts to the stream, if the following three design considerations are met: 1. The intake or collection portion of the infiltration gallery is located far enough upstream as to provide the necessary head to provide for the desired diversion rate. 2. The permeability of the existing stream bed material is tested and the envelope surrounding the intake screen is composed of a properly graded gravel. 3. The system is designed with valves and bypass piping to allow isolation of portions of the collection system to allow for flow regulation and system flushing.
Irrigation and drainage in the new millennium
Not digitized by CSUL Digital Services.
Presented at the 2000 USCID international conference, Challenges facing irrigation and drainage in the new millennium on June 20-24 in Fort Collins, Colorado.